Nilai-Nilai Islam Berkemajuan dalam Buku Ajar Pendidikan Kemuhammadiyahan SMA/SMK/MA - Arifah Cahyo Andini Suparmun; Bambang Sumardjoko; Muthoifin Muthoifin (UMSU, 2021)
Kemuhammadiyahan or Muhammadiyah education textbooks are the main learning media to transfer and internalize values for students in secondary education, which being the foundation of Muhammadiyah movement. The study aimed to describe the content, language, presentation, and graphical characteristics of progressive Islamic values in the textbooks of Kemuhammadiyahan used for senior or vocational schools (SMA/SMK,MA). This research used a qualitative library study with a philosophical approach. Data were obtained through documentation technique and were analyzed by content analysis and hermeneutics presented following the heuristics, criticism, and interpretation stages. The results show that, (1) the textual and contextual contents of faith, liberation, humanity, and justice or equality are presented in the textbooks; (2) the progressive Islamic values are presented in the sentences and paragraphs of the textbooks showing as indicated in the indicators of competences; (3) the characteristics of progressive Islamic values are described through learning objectives and materials, competency tests, independent assignments, and insights, (4) the graphical characteristics are presented in logo illustrations, covers, and documentation of organizational activities. To conclude, it can be inferred that the progressive Islamic values were textually and contextually in the mateial, examples of attitude, learning activities, and illustration.